Hematological and Biochemical Reference Intervals for Mules in Chile - Lagos, Javiera; Tadich, Tamara A. (Frontiers in Veterinary Science, 2019)
Hematological and biochemical reference intervals are an important tool for health assessment and treatment decision-making in veterinary medicine. Lack of information about reference intervals (RI) in mules force professionals to apply reference intervals developed for horses or donkeys, with the risk of misinterpretation. Thus, the aim of this study was to determine hematological and biochemical RI for healthy mules and compare them with those proposed in literature for horses, donkeys and mules. A total of 142 healthy mules (mixed breed mares × Baudet du Poitou) of both sex, all between 7 and 22 years of age and between 290 and 500 kg of live weight were sampled and 32 blood parameters analyzed in order to calculate reference intervals according to the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) and the Clinical Laboratory Standards Institute (CLSI) standards. The values obtained for Chilean mules were within the RI in three of the 21 variables where data was available for UK donkeys and for three of 22 RI available for working horses in Pakistan; no similarities were found with those from Portuguese mules. In the case of Chilean working horses RI, mules values were within range for 11 of 25 variables. The differences found in blood biochemistry may be explained by husbandry conditions, diet, type of work and biological features. Differences between mules' reference intervals and those from donkeys and working horses highlight the importance of having specific reference values for this equid hybrid and the need to develop further research in mules under different working conditions and genetic background.